Cardiomyocyte deletion of mitofusin-1 leads to mitochondrial fragmentation and improves tolerance to ROS-induced mitochondrial dysfunction and cell death - Papanicolaou, Kyriakos N. (American Physiological Society, 2012)
Molecular studies examining the impact of mitochondrial morphology on the mammalian heart have previously focused on dynamin related protein-1 (Drp-1) and mitofusin-2 (Mfn-2), while the role of the other mitofusin isoform, Mfn-1, has remained largely unexplored. In the present study, we report the generation and initial characterization of cardiomyocyte-specific Mfn-1 knockout (Mfn-1 KO) mice. Using electron microscopic analysis, we detect a greater prevalence of small, spherical mitochondria in Mfn-1 KO hearts, indicating that the absence of Mfn-1 causes a profound shift in the mitochondrial fusion/fission balance. Nevertheless, Mfn-1 KO mice exhibit normal left-ventricular function, and isolated Mfn-1 KO heart mitochondria display a normal respiratory repertoire. Mfn-1 KO myocytes are protected from mitochondrial depolarization and exhibit improved viability when challenged with reactive oxygen species (ROS) in the form of hydrogen peroxide (H(2)O(2)). Furthermore, in vitro studies detect a blunted response of KO mitochondria to undergo peroxide-induced mitochondrial permeability transition pore opening. These data suggest that Mfn-1 deletion confers protection against ROS-induced mitochondrial dysfunction. Collectively, we suggest that mitochondrial fragmentation in myocytes is not sufficient to induce heart dysfunction or trigger cardiomyocyte death. Additionally, our data suggest that endogenous levels of Mfn-1 can attenuate myocyte viability in the face of an imminent ROS overload, an effect that could be associated with the ability of Mfn-1 to remodel the outer mitochondrial membrane.